Full Day School in an Effort to Improve the Quality of Education - Nurul Aisyah (Proceeding of International Conference on Islamic Education, 2016)
Islamic schools are implementing full day school is almost spread to various regions in Indonesia. In addition to the output promising and school programs are laid out well, full day school is also an answer to concerns by parents about their children socially increasingly tense in the present era. Many false association that acted observation and child without parental control, on the other hand because parents are busy in a career that requires parents returned home late that afternoon after school child care is neglected. Full day school is a separate option for private schools in Indonesia, especially in Yogyakarta. Although the school has a full day school more hours spent in school, the output produced in accordance with the expected. However it is still said to be far from other countries. By using kaedah literature study, this article addresses the full day school as an effort to improve the quality of schools. Maximization of service, commitment, involvement of all parties, implementation of school programs that are clear, apply learning fun, extracurricular accordance with the interests of learners, scouting activities are directed, as well as the development of soft skills needed learners and strengthening technology in every activity into the basic aspects which must be done by a full day school.